2014 IEEE International Conference on Management of Innovation and Technology 2014
DOI: 10.1109/icmit.2014.6942447
|View full text |Cite
|
Sign up to set email alerts
|

Cloud computing in budget hotel management

Abstract: In the extremely competition of hotel industry in the 21th century, revenues are driven by customer satisfaction and brand loyalty. The challenge of reduced operating costs and increasing sales volume while increasing customer's satisfaction is the new stimulant for doing budget hotel business. Beginning of the 21 st century, cloud computing is probably the best solution available for the budget hotel industry in term of economic benefits. Cloud solution is ideal for a small or limited service hotel. Cloud ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Regarding AIS, hotels require reliable and accessible information transmission to gain a competitive advantage over their competitors. Hotels that can be present online by presenting the information needed by consumers and have online transaction features will have a great chance of winning the market [15]. Under these conditions, AIS plays a vital role in facilitating the availability of information both for prospective customers and management to determine future business strategies [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding AIS, hotels require reliable and accessible information transmission to gain a competitive advantage over their competitors. Hotels that can be present online by presenting the information needed by consumers and have online transaction features will have a great chance of winning the market [15]. Under these conditions, AIS plays a vital role in facilitating the availability of information both for prospective customers and management to determine future business strategies [4].…”
Section: Introductionmentioning
confidence: 99%
“…Maelah et al [4] found that cloud computing improves the quality of decision-making due to accuracy, timeliness, and integration in presenting accounting information. Integrating cloud-based AIS from various information sources or business cycles allows hotels to deliver real-time data, which, in turn, improves their managerial performance [2], [15], [16].…”
Section: Introductionmentioning
confidence: 99%